Pengaruh Konsumsi Kopi terhadap Kualitas Tidur Mahasiswa FK UKRIDA Angkatan 2021 - Pandensolang, Ariel Benaya; Hartanto, Hartanto; Evan, Evan (Jurnal MedScientiae, 2026)
Coffee is often consumed by students to enhance concentration and stamina; however, its caffeine content is known to affect sleep quality. This study aims to examine the relationship between coffee consumption and sleep quality among medical students of Universitas Kristen Krida Wacana (FK UKRIDA), class of 2021. This research is an analytical observational study with a cross-sectional approach involving 130 students as respondents. Data were collected using a coffee consumption questionnaire and the Pittsburgh Sleep Quality Index (PSQI), and analyzed using the chi-square test. The results showed that 68.5% of respondents experienced poor sleep quality, and there was a significant relationship between both the amount (p = 0.000) and duration (p = 0.001) of coffee consumption and sleep quality. It was found that consuming more than two cups per day and drinking coffee for more than two months were correlated with decreased sleep quality. In conclusion, excessive and prolonged coffee consumption significantly affects the decline in sleep quality among students, indicating the need for better education on mindful coffee intake.